Benthic fluxes in a subtropical reservoir estimated by pore-water diffusion calculation - Frascareli, Daniele [UNESP]; Cardoso-Silva, Sheila; Gontijo, Erik Sartori Jeunon [UNESP]; Melo, Darllene Silveira [UNESP]; Macedo, João Carlos Alves [UNESP]; Guandique, Manuel Enrique Gamero [UNESP]; Carlos, Viviane Moschini [UNESP]; Friese, Kurt; Rosa, André Henrique [UNESP] (Springer Nature, 2022)
The internal load of metals and nutrients in reservoirs can be derived from fluxes at the sediment–water interface via pore water (PW) and may affect the water quality. The main goal of this study was to investigate the distribution and fluxes of nutrients and metals at SWI in a subtropical reservoir. Sediments cores were collected at five sites in Itupararanga Reservoir and sliced at 1-cm depth intervals (2-cm from 6 cm deep). PW was extracted and analysed by its dissolved cations (Ca2+, Mg2+, Na+, K+) metals (Al, Ba, Cr, Cu, Fe, Mn, Ni e Zn), nutrient (total dissolved phosphorus, soluble reactive phosphorus-SRP; NO3; NH4+) and C content. The sediments were analysed by porosity, particle size distribution and contents of C, N and P. Fluxes at SWI were calculated using Fick's law in one dimension. P was being released to the water column at Core 5, by the mineralisation of OM by oxic pathways and retained at Core 2. Although Core 4 had high P concentration on PW, no results of flux was possible due to lack on bottom water data. No concentration of SRP was detected in PW of Core 1 and 7. Release of Fe, Mn, Zn and Cr was also observed. SRP was absent at the most eutrophic site (Core 1). The contribution of 74.83 mg m−2 SRP day−1 at Core 2 was potentially harmful to water quality. This study showed the importance of investigating sediment interstitial water and expanded a discussion in sub-climatic environments on the release and contribution of sediments in the geochemistry of P in aquatic ecosystems.
Keywords: Metals; Phosphorus release; Sediments; Subtropical environment